Kebijakan Maritim di Indonesia dalam Perspektif Sound Governance - Eki Darmawan; Handam Handam; Arwanto Harimas Ginting (Institut Pemerintahan Dalam Negeri, 2020)
This study examines how the world maritime axis policy (PMD) by the Indonesian State is based on the potential maritime region in need as well as the Vision of the President of Indonesia for the period 2019-2024. Using a culinary method to study a variety of existing literature and analyzed in the perspective of Good Governance. This study produces an analysis; The first; marine inclusiveness policy as a state policy involving various levels of actors to access to marginalized groups and or regions so far on marine potential. The second; Making the maritime axis as the main source of the economy to improve welfare. The third; marine resources are made as the world's maritime axis, with the involvement of various countries in the Indo-Pacific region specifically as actors involved in the use and development of the world's maritime axis. Key Words; Sound Governance, Fisheries Policy, World’s Maritime Axis.